2021
DOI: 10.1101/2021.12.17.473144
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“Heat waves” experienced during larval life have species-specific consequences on life-history traits and sexual development in anuran amphibians

Abstract: Extreme temperatures during heat waves can induce mass-mortality events, but can also exert sublethal negative effects by compromising life-history traits and derailing sexual development. Ectothermic animals may, however, also benefit from increased temperatures via enhanced physiological performance and the suppression of cold-adapted pathogens. Therefore, it is crucial to address how the intensity and timing of naturally occurring or human-induced heat waves affect life-history traits and sexual development… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 109 publications
1
3
0
Order By: Relevance
“…If sex reversal in free‐living amphibians occurs mostly due to extreme temperatures (Lambert et al, 2018; Mikó et al, 2021), the lack of sex reversal in common toads might be explained by their higher tolerance to heat. In line with this idea, the breeding season starts ~1 month later in spring for common toads than for agile frogs in our study region; accordingly, we found female‐to‐male sex reversal in agile frogs (Nemesházi et al, 2020) but not in common toads among free‐living adults, and we found the same difference between the two species in an experimental study of heat‐induced sex reversal (Ujszegi et al, 2021). Similarly, evolution of different temperature thresholds for sex reversal was suggested to explain the finding that in a reptile, Pogona vitticeps , sex reversal is absent in the hottest part of the species’ range (Castelli et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…If sex reversal in free‐living amphibians occurs mostly due to extreme temperatures (Lambert et al, 2018; Mikó et al, 2021), the lack of sex reversal in common toads might be explained by their higher tolerance to heat. In line with this idea, the breeding season starts ~1 month later in spring for common toads than for agile frogs in our study region; accordingly, we found female‐to‐male sex reversal in agile frogs (Nemesházi et al, 2020) but not in common toads among free‐living adults, and we found the same difference between the two species in an experimental study of heat‐induced sex reversal (Ujszegi et al, 2021). Similarly, evolution of different temperature thresholds for sex reversal was suggested to explain the finding that in a reptile, Pogona vitticeps , sex reversal is absent in the hottest part of the species’ range (Castelli et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…For example, we recently found that sex ratio in the toad Bufo bufo (ZW/ZZ) was not affected by exposure to 30°C, a temperature high enough to cause up to 100% female‐to‐male sex reversal in the frog Rana dalmatina (XX/XY) in the same experiment. [ 51 ] This contradicted the broadly cited study by Piquet, [ 53 ] where 25°C produced male excess in Bufo vulgaris (a synonym for Bufo bufo ). The contradiction can be resolved by realizing that Piquet captured her animals near Geneva, in a hybrid zone of Bufo bufo and Bufo spinosus , [ 78 ] two species that were thought to be one at the time.…”
Section: The Devil In the Details: How To Choose Suitable Methods?mentioning
confidence: 86%
“…[ 12 ] Detailed searching methods are described in Supplement 1, and the data extracted in Supplementary Table 1. We found only four experiments in which anuran species with both male and female heterogamety were studied for sex‐reversal propensity, [ 22,49–51 ] although heterogamety was not in their focus. Other studies were usually restricted to a single species.…”
Section: Experimental Evidence For ‘‘Asymmetrical Sex Reversal’’mentioning
confidence: 99%
“…On day 20, we started thermal treatments as described in Ujszegi et al [52] (for details, including slight modifications, see the Supplementary material) and monitored tadpoles daily to record any mortality events. Water temperatures were kept at 22, 28, and 30 °C in the three thermal treatment groups, respectively (Table S1).…”
Section: Methodsmentioning
confidence: 99%